Utilization of Rubber Factory WWTP Muds as Fertilizer for Rubber Plant Clone PB 260 (Hevea Brasiliensis Muell. Arg) - Anis Tatik Maryani; Suri Setyaningsih Dewi; Nyimas Mirna Elsa Fathia; Yudha Gusti Wibowo (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2022)
The rubber plant (Hevea brasiliensis Muell. Arg) is an important plantation crop in Indonesia because it is one of the non-oil and gas products that are a source of large amounts of foreign exchange income for the country. Experiment was arranged in a Randomized Block Design with one factor, namely Compost for Wastewater Treatment Plant (WWTP) sludge from a rubber factory which consisted of 5 treatment levels. Statistical analysis was carried out using variance (ANOVA). Variables observed in rubber plants were an increase in bud grafting length, plant diameter, the number of leaves, shoot dry weight, and root dry weight. The results showed that the WWTP waste compost from the rubber factory affected the growth of rubber seedlings, as shown in the variable length of grafting shoots, the number of leaf stalks (strands), and the dry weight of the plant crown. Meanwhile, the increase in stem diameter and dry weight of plant roots showed no significant effect on the observed variables.